Proses pembuatan gate hollow dengan menggunakan mesin bor radial Csepel tipe RF 22/B - Difqi Faza Umary Difqi; Deddy Supriyatna (Jurnal Teknik Mesin Indonesia, 2023)
The machining process or can be called the manufacturing process is a process of producing raw materials or finished materials that are converted into the desired goods. One of the processes in the manufacturing industry is the drilling process. The purpose of this research is to know the process of using a radial drilling machine in making hollow gates and to find out what errors occur when the process of making hollow gates takes place. This research uses the method of literature study and field research (field research). The results show that based on the entire process of making a hollow gate, an error was obtained in the process of making a hollow gate regarding the diameter of the hole which should have been 15 mm to 18 mm and there was an error between the distances of the holes that had been made.